Immunohistochemical assay for neuron-specific enolase, synaptophysin, and RB-associated protein as a diagnostic aid in advanced retinoblastomas - López López JC (Dove Medical Press, 2018)
José Carlos López López,1 Nieves Fernández Alonso,1 Juan Cuevas Álvarez,1,2 Tomás García-Caballero,2 José Carlos Pastor Jimeno3 1Ocular Pathology Laboratory, Instituto Universitario de Oftalmobiología Aplicada (IOBA), University of Valladolid, Valladolid, Spain; 2Department of Pathology, Hospital Clínico Universitario, Santiago de Compostela, Spain; 3Retina Group, Instituto Universitario de Oftalmobiología Aplicada (IOBA), University of Valladolid, Hospital Clínico Universitario, Valladolid, Spain Purpose: We evaluated the expression of the neural markers, neuron-specific enolase, and synaptophysin, as a tool to confirm the diagnosis of retinoblastoma (RB) in undifferentiated and advanced tumors. Additionally, we determined whether the extent of RB-associated protein (pRb) expression is helpful in assessing the prognosis in RB patients. Methods: Conventional whole tissue section and tissue microarray immunohistochemistry for neuron-specific enolase, synaptophysin, and pRb were carried out in a series of 22 RBs. Results: Neuron-specific enolase and synaptophysin were expressed in 75%–100% of the tumor cells, and the staining intensity was strong. Two RBs expressed pRb in 75%–100% of the tumor cells, also with strong staining intensity. Concordance between the immunohistochemical outcomes for whole tissue staining and tissue microarray staining was 76.2% for neuron-specific enolase, 85.7% for synaptophysin, and 80.0% for pRb. Conclusion: Neuron-specific enolase and synaptophysin have the potential to be useful markers for the diagnosis of RBs. Extensive and strong pRb staining is not associated with less aggressive tumor behavior according to the pathologic classification of RBs. Keywords: retinoblastoma, immunohistochemistry, neuron-specific enolase, synaptophysin, pRb